From the Particular to the Beyond: Christian Educator’s Identity Reimagined - Philips, Gerardette (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2024)
One may not have answers to questions regarding identity solely by looking at one’s own self while neglecting its connection to others. Against the background of the more intricate world of today, it is necessary that a spiritual reflection on identity should begin by looking inward, that is, into what is particular in one’s self wherein one can find a connection to God, the Creator who created human beings in his image. This religious truth can manifest through various paths, especially through the particular role of a Christian educator. This article goes through this process of recognising identity in oneself that can move a person beyond personal identity towards relational identity: an awareness of being connected to the whole creation. Only when one has undergone this can one perform the act of crossing borders without doing away with one’s own identity. This article presents a perspective of how identity can be understood differently today.